PENERAPAN REGRESI LOGISTIK HIERARKI BINER UNTUK MENENTUKAN DETERMINAN KEMISKINAN DI BENGKULU DENGAN MENGGUNAKAN INDEKS AKSESIBILTAS SARANA UMUM (IASU) SEBAGAI VARIABEL KENTEKSTUAL - Yoga Dwi Nugroho (Jurnal Statistika Universitas Muhammadiyah Semarang, 2018)
Poverty is the condition which a person or community is being not able to fulfill basic needs in various dimension of life. Bengkulu is a province that located in the west of Indonesia and has high levelof poverty. Eradicating poverty needs a right policy from the government and therefore proper data analysis for knowing the determinants of poverty. This study aim to analyze poverty pattern and knowing the determinant of poverty in Bengkulu province using binary hierarcy logistic regression. There are sixindependent variables for first level (household) : area classification, size of family, sex of household head, age of household head, job of household head and the education of household head. Variable for second level (regency) is accessibility of public facility index (IASU) as contextual variable. Dependent variabel is the status of poverty According to the study, the significant variables as determinant of poverty are size offamily, sex of household head, education of household head and IASU.  Keywords : Poverty, IASU, Binary Hierarchy Logit Regression